1992
DOI: 10.1016/0735-1097(92)90624-v
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of colchicine for the prevention of restenosis after coronary angioplasty

Abstract: Colchicine, an antimitogenic agent, has shown promise in preventing restenosis after coronary angioplasty in experimental animal models. A prospective trial was conducted involving 197 patients randomized in a 2:1 fashion to treatment with oral colchicine, 0.6 mg twice daily (130 patients), or placebo (67 patients) for 6 months after elective coronary angioplasty. Treatment in all patients began between 12 h before angioplasty and 24 h after angioplasty. Compliance monitoring revealed that 96% of all prescribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
7

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(113 citation statements)
references
References 15 publications
0
106
0
7
Order By: Relevance
“…13 A variety of pharmacologic means have been tested in an attempt to control SMC proliferation after vascular injury. Clinical trials of drugs including antiplatelet agents, 1415 anticoagulants, 16 corticosteroids, 17 calcium channel blocking agents, 18 and colchicine 19 have proven unsuccessful in reducing restenosis rates. Heparin has been consistently successful in controlling SMC proliferation in experimental models, both systemically administered 20 - 21 and locally applied to the vessel.…”
Section: Gamma Irradiation Inhibits Neointimal Hyperplasia In Rats Afmentioning
confidence: 99%
“…13 A variety of pharmacologic means have been tested in an attempt to control SMC proliferation after vascular injury. Clinical trials of drugs including antiplatelet agents, 1415 anticoagulants, 16 corticosteroids, 17 calcium channel blocking agents, 18 and colchicine 19 have proven unsuccessful in reducing restenosis rates. Heparin has been consistently successful in controlling SMC proliferation in experimental models, both systemically administered 20 - 21 and locally applied to the vessel.…”
Section: Gamma Irradiation Inhibits Neointimal Hyperplasia In Rats Afmentioning
confidence: 99%
“…[1][2][3][4] Numerous attempts to modify the fibroproliferative response to arterial injury, either through pharmacological interventions or mechanical devices, have met with very limited success. [5][6][7][8][9] This failure reflects, in part, the complexity of the pathophysiological process of neointima formation after balloon injury and the difficulty in identifying the appropriate cellular or molecular target(s) for therapeutic intervention. 10 -12 An understanding of the events involved in ECM remodeling, which is required for VSMC migration and, possibly, proliferation, 13 may provide additional targets for modifying restenosis.…”
mentioning
confidence: 99%
“…Colchicine is quickly cleared after systemic administration, and this may account for its lack of clinical effect in clinical studies. There was a high patient drop-out rate in the clinical trials, due to adverse side effects (despite a reduction in dose from that found optimal in animal studies) [23,73,76,229,231]. While an infusion of colchicine via a balloon catheter did not have a long dwell time in rabbit artery walls, its retention was improved by containment within microparticles, resulting in a decrease in neointimal thickening [232].…”
Section: Cytostatic and Immunosuppressivementioning
confidence: 99%
“…Restenosis has been characterised as a return to ≥70% stenosis and loss of ≥50% of initial gain; the loss of ≥0.7 mm of the vessel diameter; ≥50% stenosis; loss of 50% of initial gain; 50-75% stenosis; % loss of initial gain; change from <50% to ≥50% stenosis; ≥50% stenosis and >50% of initial gain or >20% luminal diameter; or the recurrence of clinical symptoms or adverse events. Binary stenosis divides the cohort of patients (or blockages) into those with <50% stenosis and those with ≥50% stenosis (regardless of initial gain) [5,8,14,21,22,46,53,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Vein graft disease is usually measured as % stenosis.…”
Section: What Are Restenosis and Vein Graft Disease?mentioning
confidence: 99%